Africa’s Space Technology Investment and Socio-Economic Returns: The Case of Nigeria - Okon, Emmanuel O. (International Journal of Business and Management Future, 2018)
Scientific and technological advances and innovations are fundamental to sustained economic and human development. Space exploration programs offer significant potential socio-economic benefits. Unfortunately, in Nigeria, space programme is considered to be less necessary than many other governmental initiatives, particularly in the context of sustainable development. This paper takes a look at space technology investment in Africa and application of space technology in solving socio-economic problems in the continent with a special focus on Nigeria. Also, the paper identified some challenge faced in the Nigerian space programme and made some suggestion. Nigeria must take advantage of innovations in space technology to utilize space and the by-products of space technology to make significant strides in optimizing the resources of socio-economic development and solve national problems in consonance with the global sustainable development agenda.